In vivo footprinting and high-resolution methylation analysis of the mouse hypoxanthine phosphoribosyltransferase gene 5' region on the active and inactive X chromosomes. - Litt, M D (1996)
To investigate potential mechanisms regulating the hypoxanthine phosphoribosyltransferase (HPRT) gene by X-chromosome inactivation, we performed in vivo footprinting and high-resolution DNA methylation analysis on the 5' region of the active and inactive mouse HPRT alleles and compared these results with those from the human HPRT gene. We found multiple footprinted sites on the active mouse HPRT allele and no footprints on the inactive allele. Comparison of the footprint patterns of the mouse and human HPRT genes demonstrated that the in vivo binding of regulatory proteins between these species is generally conserved but not identical. Detailed nucleotide sequence comparison of footprinted regions in the mouse and human genes revealed a novel 9-bp sequence associated with transcription factor binding near the transcription sites of both genes, suggesting the identification of a new conserved initiator element. Ligation-mediated PCR genomic sequencing showed that all CpG dinucleotides examined on the active allele are unmethylated, while the majority of CpGs on the inactive allele are methylated and interspersed with a few hypomethylated sites. This pattern of methylation on the inactive mouse allele is notably different from the unusual methylation pattern of the inactive human gene, which exhibited strong hypomethylation specifically at GC boxes. These studies, in conjunction with other genomic sequencing studies of X-linked genes, demonstrate that (i) the active alleles are essentially unmethylated, (ii) the inactive alleles are hypermethylated, and (iii) the high-resolution methylation patterns of the hypermethylated inactive alleles are not strictly conserved. There is no obvious correlation between the pattern of methylated sites on the inactive alleles and the pattern of binding sites for transcription factors on the active alleles. These results are discussed in relationship to potential mechanisms of transcriptional regulation by X-chromosome inactivation.